2007
DOI: 10.1002/ardp.200600191
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinate Inhibitors of UDP‐N‐Acetylmuramoyl‐L‐Alanyl‐D‐Glutamate: L‐Lysine Ligase (MurE)

Abstract: The increasing emergence of pathogenic bacterial strains with high resistance to antibiotic therapy has created an urgent need for the development of new antibacterial agents that are directed towards novel targets. We have focused our attention on the Mur ligases (MurC-F), which catalyze the early steps of bacterial peptidoglycan biosynthesis, and which to date represent under-exploited targets for antibacterial drug design. We show that some of our phosphinate inhibitors of UDP-N-acetylmuramoyl-L-alanyl:D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Promisingly, Strancar et al . reported that some phosphinate inhibitors of MurD also inhibit MurE with IC 50 values in the micromolar range (Strancar et al ., ). Sulphonamide derivatives based on naphthalene‐ N ‐sulphonyl‐ d ‐glutamic have then been designed as transition‐state analogue inhibitors of MurD (Kotnik et al ., ; Humljan et al ., ; Sosic et al ., ; Simcic et al ., ).…”
Section: Development Of Multi‐target Mur Ligase Inhibitorsmentioning
confidence: 97%
“…Promisingly, Strancar et al . reported that some phosphinate inhibitors of MurD also inhibit MurE with IC 50 values in the micromolar range (Strancar et al ., ). Sulphonamide derivatives based on naphthalene‐ N ‐sulphonyl‐ d ‐glutamic have then been designed as transition‐state analogue inhibitors of MurD (Kotnik et al ., ; Humljan et al ., ; Sosic et al ., ; Simcic et al ., ).…”
Section: Development Of Multi‐target Mur Ligase Inhibitorsmentioning
confidence: 97%
“…Its high (stereo)specificity for D-glutamic acid has been shown by studying structurally related analogues tested as substrates or inhibitors. 21,22 There have been several successful attempts to identify MurD inhibitors by using the transition-state hypothesis [23][24][25][26][27][28][29] and it was suggested that D-glutamic acid represents an essential fragment of a potent inhibitor. 25,26 Based on this rationale we recently synthesized a series of sulfonamide derivatives of D-glutamic acid, as analogues of the tetrahedral intermediate (unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…The UDP-MurNAc:L-alanine ligase (MurC), encoded by the murC gene, represents such an interesting candidate for drug development (9,10). Recently, different phosphinic acid derivatives and substrate analogues have been identified as Mur ligase inhibitors (11,12).…”
mentioning
confidence: 99%